2008
DOI: 10.1590/s1677-04202008000400006
|View full text |Cite
|
Sign up to set email alerts
|

Level and distribution of 20-hydroxyecdysone during Pfaffia glomerata development

Abstract: The ecdysteroid 20-hydroxyecdysone (20E) is a steroid hormone found in insects and few plants. To analyze its temporal and spatial distribution in Pfaffia glomerata (Amaranthaceae), we selected among 71 accessions, the accession 13 which showed the highest root 20E total quantity (1.48 g/plant root). The 20E was constantly detected in flowers, leaves, stems, and roots, but its percentage was variable throughout its development. The highest 20E percentage was found in flowers (0.82%), roots (0.66%), leaves (0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…Methanolic extracts from 3 independent samples were prepared with 100 mg of powdered plant material in 10 mL of methanol, and incubated at 25°C under agitation for 7 days. Quantification of 20E in the methanolic extract was performed using High Performance Liquid Chromatography (HPLC) according to Festucci-Buselli et al (2008b). The calibration curve was obtained by adding the standard 20-hydroxyecdysone (Sigma-Aldrich) to methanol at 20, 40, 60, 80, 100, 125, 150, and 200 mg L -1 .…”
Section: Hplc Determination Of 20-hydroxyecdysone (20e)mentioning
confidence: 99%
“…Methanolic extracts from 3 independent samples were prepared with 100 mg of powdered plant material in 10 mL of methanol, and incubated at 25°C under agitation for 7 days. Quantification of 20E in the methanolic extract was performed using High Performance Liquid Chromatography (HPLC) according to Festucci-Buselli et al (2008b). The calibration curve was obtained by adding the standard 20-hydroxyecdysone (Sigma-Aldrich) to methanol at 20, 40, 60, 80, 100, 125, 150, and 200 mg L -1 .…”
Section: Hplc Determination Of 20-hydroxyecdysone (20e)mentioning
confidence: 99%
“…Phytoecdysteroids have been found in different concentrations in many plants belonging to the Amaranthaceae family (Savchenko et al 1998), including the Pfaffia species Pfaffia iresinoides (Nishimoto et al 1987) and P. glomerata (Shiobara et al 1993). Despite the differing capacities of plant organs for phytoecdysteroid accumulation (Savchenko et al 1998), β-ecdysone content in P. glomerata has been almost exclusively been analyzed in roots (Festucci-Buselli et al 2008), which have been utilized as raw material by the phytotherapeutic industry. In the present study, HPLC analysis of methanolic extracts from P. glomerata and P. tuberosa showed that both roots and aerial parts contained a significant amount of β-ecdysone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In general, important tissues/organs for plant survival contain a higher concentration of phytoecdysteroids, which is probably due to the protective effect of these compounds against insects (Dinan 2001;Klein 2004). Interestingly, Festucci-Buselli et al (2008) recently reported that the stem and leaf total of 20-hydroxyecdysone (20E) content in P. glomerata remained constant, showing little variation, while root total 20E content increased over time, suggesting that 20E may accumulate in roots. HPLC chromatograms of β-ecdysone detected in the roots of P. glomerata BRA genotype are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations